REVITALISASI FUNGSI MASJID SEBAGAI PUSAT EKONOMI DAN DAKWAH MULTIKULTURAL - Dalmeri Dalmeri (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2014)
This article had the purpose to analyze the functions of the mosque that is not only as a center of activities of ibadah, but also as the center of da‘wa and Muslim social and economic activities. The orientation of da‘wa that emphasized individual improvement dealing with in the quality of faith have neglected one important dimension of da‘wa, namely the development and empowerment of the Muslims as a whole. Through a qualitative descriptive approach and collecting data through observation and interviews, it was founded that communities which are empowered are not seen as passive recipient of the service, but a community that has a variety of potential and capabilities that can be empowered. Muslim community empowerment activities can be done through mentoring by boasting motivation, increasing awareness, developing knowledge and attitudes to enhance their capabilities, mobilizing productive resources and developing economic and da‘wa activity.